Analysis of regulatory T lymphocytes in fungal infections - S. V. Popov (SPb RAACI, 2021)
Morbidity and mortality rates in invasive mycoses determine the need to improve methods for their timely diagnosis by assessment the patients’ immune status. Evaluation of individual immune status allows the clinician to predict the development and course of fungal infections. At the same time, identification of opportunistic mycosis in immunocompetent patients should require a search for some hidden immune deficiency. Determining the cause of such immune defects can help develop an effective strategy for both etiotropic and immune therapy of patients with invasive mycoses. Currently, the functions of regulatory T lymphocytes that support immunological tolerance in fungal infections remain to be incompletely studied. In this review, we present experimental works which suggest that the regulatory T lymphocytes are able to suppress immune responses to fungi by stimulating the immunosuppressive environment. It was shown that regulatory T lymphocytes use Toll-like receptor 2 to achieve immunosuppression in Candida infections. The balance between the number and function of regulatory T lymphocytes is essential for elimination of fungal pathogens and protection against post-infectious immunopathological conditions. It was found that the regulatory T lymphocytes provide protection at an early stage of Candida infection, since, due to IL-2 suppression, they enhance Th17 differentiation and clearance of fungi. Moreover, at the later stages of infection, the regulatory T lymphocytes have an inhibitory effect. The balance between Th17 and regulatory T lymphocytes in mucosal lining is considered the main factor for distinguishing between commensal carriage and Candida albicans infection. The study is presented which indicate that disseminated candidiasis associated with expansion of regulatory T lymphocytes stimulates a Th17-cell response that controls the course of the disease. The mechanisms that control regulatory T lymphocytes homeostasis are essential for providing effective protection against pathogens, as well as for controlling the immunopathological conditions associated with Candida infection. The review presents data that have established the role of TGF-β1 in increasing the viability of regulatory T lymphocytes, which is correlated with the pronounced immunomodulating role of these cells at the later phase of Candida infections of the mucous membrane. It has been also demonstrated that the pulmonary regulatory Tlymphocytes are induced during cryptococcal infection, which predominantly suppresses Th2 cells, thereby supporting its course. Expansion of the regulatory T lymphocytes upon administration of IL-2/antiIL-2 complex during cryptococcal infection led to a decrease in IgE production and a decrease in allergic airway inflammation. It should be noted that refinement of prognostic value of the regulatory T lymphocytes in human fungal infections may substantiate the basic principles of targeted immunotherapy.